2009
DOI: 10.1002/hbm.20766
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between phase‐locked and nonphase‐locked alpha oscillations in a working memory task

Abstract: The functions of human alpha oscillations ( approximately 10 Hz) were related to cognitive processes such as memory and top-down control. Recent models suggest that alpha phase serves as a mechanism especially relevant for the timing of neural activity, whereas alpha amplitude is important for the inhibition of task-irrelevant brain areas. This study investigates directly the influence of top-down modulation on phase-locked and nonphase-locked alpha rhythms. We conducted an EEG experiment where subjects perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(90 citation statements)
references
References 42 publications
(63 reference statements)
12
74
0
Order By: Relevance
“…More importantly, the application of rTMS (at alpha frequencies) over cortical sites processing irrelevant information led to increments in WM performance. Relatedly, when participants successfully ignore taskirrelevant stimuli, alpha amplitudes increase already prior to stimulus-onset (Freunberger et al, 2009) (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…More importantly, the application of rTMS (at alpha frequencies) over cortical sites processing irrelevant information led to increments in WM performance. Relatedly, when participants successfully ignore taskirrelevant stimuli, alpha amplitudes increase already prior to stimulus-onset (Freunberger et al, 2009) (Fig. 1).…”
Section: Introductionmentioning
confidence: 92%
“…One important factor contributing to interindividual differences in the WM performance range is the efficient control of WM contents (Freunberger et al, 2009;Gazzaley et al, , 2008Sauseng et al, 2009;Vogel et al, 2005), in particular, when both relevant and irrelevant information is present in the environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the above studies linking alpha oscillations with WM quantity, two new studies have indicated their role in WM precision [70,71] , so it cannot be ruled out that alpha oscillations are also correlated with WM quality. Future studies to disentangle the roles of alpha power and phase would help to answer this question, since it has been shown that the phase-locked and non-phaselocked parts of alpha oscillations are related to different processes during WM [72] .…”
Section: Neural Oscillations Serve the Interaction Between Pfc And Sementioning
confidence: 99%